(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background : Fetus in fetu is a rare congenital anomaly in which a malformed fetus or parasitic fetus grows within the body of its twin. It is a parasitic twin of a Diamniotic, monozygotic twin. Fetus in fetu is often overlooked in the differential diagnosis of an abdominal mass in infants and children. Teratoma is one of the closest differentials and must be excluded. Unlike teratomas, fetus in fetu is a benign disorder. The objective of our study is to describe the sonographic findings of an extremely rare pathology. We therefore the present diagnosis, pathology, management of fetus-in-fetu. Case Presentation: On 6th June 2021, a two years boy was brought by his parents to Chittagong Medical College Hospital (CMCH) for treatment with the complains of abdominal mass, occasional abdominal pain and loss of appetite. The patient was evaluated radiologically by plain radiographs, USG and pre & post contrast CT scan of the abdomen. All radiological modalities showed a mass in the left lumber region having internal bony structures likelong bone, vertebra and teeth. CT scan played the vital role in clearly demonstrating the bones and confirming the presence of vertebra. Radiologically a diagnosis was made as fetus-in-fetu and the possibility of Teratoma was excluded by the presence of vertebra. The patient underwent surgery and the mass was completely excised. A deformed parasitic fetus enclosed in a complete capsule was removed from the patient’s abdominal cavity. Autopsy of the specimen showed deformed limbs, presence of vertebra, long bone, other soft tissue, organogenesis around an axis and histopathology confirmed the presence of vertebra, bone and bone marrow, cardiac muscle, nerve tissue, intestine, renal tubules with glomerulus, lymphoid tissue, respiratory epithelium and skin. All findings were compatible with fetus-in-fetu. Conclusion : Although fetus in fetu is a rare condition, correct diagnosis using imaging can be made before surgery. It should be considered as a diffential diagnosis for lump abdomen especially in infant. Complete excision is curative. JCMCTA 2021 ; 32 (2) : 151-155